Pola perkembangan morfologi fisik kota di cekungan bandung periode 2009 – 2018 - Ramadhan Pasca Wijaya; Bowo Susilo; Prima Widayani (Jurnal Teknosains, 2020)
Land development will be occur from time to time, the developments phenomenon will have either positive or negative impact. The impact of this phenomenon will affect various aspects, such as socioeconomic, mobility, land quality, and more. So the study on land development is required to evaluate and anticipate the negative impact on some region. To do evaluating and anticipating unwanted impacts a study can be carried out to become the basis for regional development or regional planning. one of them is to examine the pattern of urban development that will be used as a reference for regional development planning that will occur in the future. This study aims to analyze the development of urban physical morphology in Bandung Basin period 2009 - 2018. The method in this research is quantitative descriptive in the form of data collecting, data processing, modelling, and mapping. The research method is quantitative and qualitative in the form of data collection, data processing, modeling and mapping. The method of applying quadrant and burgess models to find the value of built-up land density that can reflect information on the phenomenon of built-up area development seen from the built-up area density in each agreed zone with geometric and quadrant models. The results in this research shows that the morphological structure of developed land in Bandung Basin is concentric with the highest density of 0.3459 km² which is centered in Cimahi and Bandung, also development is elongated and along the road with the majority of the land development create a leapfrog pattern, so it can be concluded that urban morphology in Bandung Basin is concentric with the linear development which is leapfrog.